Hypotension and Bradycardia Following Papaverine Installation During Intracranial Aneurysm Surgery: A Report of Three Cases - Al-Sharshahi, Zahraa F.; Hoz, Samer S.; Almurayati, Mustafa E.; Ghanim, Teeba M.; Kareem, Zahraa M.; Alsubaihawi, Zahraa A. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction One of the major complications of intracranial aneurysm surgery is vasospasm. Papaverine is an effective vasodilator that can be instilled directly onto the vessels in the operative field with the aim of preventing intraoperative and postoperative vasospasm. Several case reports of hemodynamic instability in general and of hypotension, in particular, were reported after the use of topical papaverine during aneurysm clipping surgery.Case description Herein, we report three cases of transient profound hypotension and relative bradycardia after intracisternal papaverine usage during ruptured anterior communicating artery aneurysm clipping surgery.Conclusion Caution should be taken while using papaverine intracisternally during anterior circulation aneurysm clipping, since it may cause several serious complications, including profound hemodynamic instability, particularly when instilling on a fenestrated lamina terminalis.
Keywords: intracisternal papaverine; lamina terminalis; aneurysm surgery; hypotension